Relation of the hepatic lipase gene C-514T polymorphism with nutritional indicators and lipoproteins in a Peruvian population sample: a nutrigenetic perspective - Huerta, Doris (2008)
Introduction: Cardiovascular diseases are major causes de death in the world.The hepatic lipase (HL) gene promoter region presents a C-514T functionalpolymorphism related to enzyme activity, variation of lipoproteins levels andpossible cardiovascular disease risk. Objectives: To determine the associationof HL gene promoter region polymorphism with both nutritional indicators andlipoproteins levels in a healthy Peruvian sample. Design: Descriptive, transversal,associative study. Setting: Alberto Guzman Barron Biochemistry and NutritionResearch Center, Faculty of Medicine, Universidad Nacional Mayor de San Marcos.Participants: Ninety healthy male and female volunteers aged 18 to 58 years.Interventions: Genomic DNA was obtained from serum samples accordingto standard methodology. Anthropometric measurements and lipid profile byenzymatic methods were performed. Polymorphism C-514T in the HL gene wasdetermined by polymerase chain reaction (PCR). PCR products were digestedwith NlaIII and fragments separated by polyacrilamyde gel electrophoresis (PAGE)and stained with silver nitrate. Main outcome measures: HL gene genotypesand alleles frequencies and relation with both lipid and nutritional parameters.Results: We found genotype frequencies CC=0,143; CT=0,593 and TT = 0,264,consistent with Hardy-Weinberg equilibrium (X2 =3,8024, g.l. = 1, p = 0,086).Alleles frequencies were C allele = 0,4395 and T allele = 0,5605. HDLc, LDLc,TAG cholesterol levels and subcutaneous fold, BMI and fat percentage averagesin CC, CT and TT genotypes did not show significant differences (p>0,05).Nevertheless, when T allele was analyzed alone (genotypes CT and TT) accordingto age and sex there were significant differences (p<0,05) in some parameters.Conclusions: CT heterozygote and T allele, related to HL low activity were themost frequent genotypes in this Peruvian sample; in addition, presence of Tallele was associated with variations in lipoprotein levels and nutritional factorswhich could have influence on cardiovascular diseases.